2016
DOI: 10.21786/bbrc/9.1/8
|View full text |Cite
|
Sign up to set email alerts
|

Application of bioinformatics in the prediction and identifi cation of potential antimicrobial peptides from Curcuma longa

Abstract: Irrigation water has become less available in many regions due to global climate change and an increased competition for water by industry, domestic purposes, and the environment. To confront this challenge, there is an urgent need to develop water-saving irrigation strategies and techniques in order to maximize crop water use effi ciency (WUE). In the other hand over-fertilization of mobile nutrients like nitrogen (N) may lead to leaching beyond root zone under plentiful irrigation, while it may decrease yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Regardless of the peptide length, the accuracy of the prediction of these algorithms is between 87% and 93%, and an AMP sequence has a score within 0.5-1.0. [20,38] Since the Lys-substituted sequence had better AMP probability scores than the Arg-substituted one, PL-101-WK was selected for experimental assays. The BLAST searching of the CAMP R3 database displayed that sequence with GI number 914817640 was the most similar one to PL-101-WK with 88% similarity and 63% identity.…”
Section: Design and Characterization Of Peptidesmentioning
confidence: 99%
“…Regardless of the peptide length, the accuracy of the prediction of these algorithms is between 87% and 93%, and an AMP sequence has a score within 0.5-1.0. [20,38] Since the Lys-substituted sequence had better AMP probability scores than the Arg-substituted one, PL-101-WK was selected for experimental assays. The BLAST searching of the CAMP R3 database displayed that sequence with GI number 914817640 was the most similar one to PL-101-WK with 88% similarity and 63% identity.…”
Section: Design and Characterization Of Peptidesmentioning
confidence: 99%
“…Firstly, the removal of two residues and the subsequence single point substitutions were planned in the N-terminal region of 1018-K6 sequence, as it was reported that the substitution of any residues at the positions Val7-Arg12 in the parent peptide (NH2-VRLIVKVRIWRR-CONH2) substantially reduced the antimicrobial activity and were mostly not favorable [21,22]. To this aim, the following criteria were adopted: (i) deletion of a Val residue, as the analysis of amino acid frequency in the AMPs available at CAMP database revealed that this amino acid was less often encountered [23]; (ii) deletion of a further neutral amino acid between Iso or Leu to conserve unaltered the net positive charge, since it is essential for the interactions with the negatively charged membranes of bacteria; (iii) replacement of one neutral amino acid with Trp residue to enhance the total Trp ratio and the hydropathicity, which are key physicochemical parameters influencing the ability of several AMPs to adopt an amphipathic conformation upon binding to the bacterial membrane [24,25]; (iv) conservation of at least an Arg residue, as it has been observed that this amino acid strongly improves the antibacterial activity, due to its enhanced membrane permeability with respect to Lys [26].…”
Section: Design Of New Ampsmentioning
confidence: 99%